When Jihadi Ideology Meets Social Media - Ammar, Jamil (Springer International Publishing, 2018)
This book is designed to provide specialists, spectators, and students with a brief and engaging exploration of media usage by radical groups and the laws regulating these grey areas of Jihadi propaganda activities. The authors investigate the use of religion to advance political agendas and the legal challenges involved with balancing regulation with free speech rights. The project also examines the reasons behind the limited success of leading initiatives to curb the surge of online extreme speech, such as Google's "Redirect Method" or the U.S. State Department's campaign called "Think Again." The volume concludes by outlining a number of promising technical approaches that can potently empower tech companies to reduce religious extremist groups' presence and impact on social media.